Energy expenditure in adolescents playing new generation computer games. Issue 7 (7th July 2008) - Graves, Lee; Stratton, Gareth; Ridgers, N D; Cable, N T
Abstract : Objective: To compare the energy expenditure of adolescents when playing sedentary and new generation active computer games. Design: Cross sectional comparison of four computer games. Setting Research laboratories. Participants: Six boys and five girls aged 13–15 years. Procedure: Participants were fitted with a monitoring device validated to predict energy expenditure. They played four computer games for 15 minutes each. One of the games was sedentary (XBOX 360) and the other three were active (Wii Sports). Main outcome measure: Predicted energy expenditure, compared using repeated measures analysis of variance. Results: Mean (standard deviation) predicted energy expenditure when playing Wii Sports bowling (190.6 (22.2) kl/kg/min), tennis (202.5 (31.5) kl/kg/min), and boxing (198.1 (33.9) kl/kg/min) was significantly greater than when playing sedentary games (125.5 (13.7) kl/kg/min) (P<0.001). Predicted energy expenditure was at least 65.1 (95% confidence interval 47.3 to 82.9) kl/kg/min greater when playing active rather than sedentary games. Conclusions: Playing new generation active computer games uses significantly more energy than playing sedentary computer games but not as much energy as playing the sport itself. The energy used when playing active Wii Sports games was not of high enough intensity to contribute towards the recommended daily amount of exercise in children.